Systematic Literature Review : Strategi Supervisi yang Inovatif untuk Meningkatkan Kepemimpinan Pendidikan di Sekolah - Eka Wahyuni Nur'rohim (Journal of Innovation in Teaching and Instructional Media, 2025)
This study aims to identify innovative educational supervision strategies that are effective in improving educational leadership, particularly the competencies of teachers and principals. This study used the Systematic Literature Review (SLR) method by analyzing 15 national articles published between 2017 and 2025. Data were collected through a systematic search of academic databases, then analyzed thematically to identify patterns and key findings. The results indicate that collaborative supervision and technology-based supervision approaches are the most effective strategies in improving teachers’ pedagogical and professional competencies. Collaborative supervision encourages active teacher participation, while technology-based supervision expands access and efficiency of the supervision process. This study provides an up-to-date systematic review of innovative supervision strategies in the national education context, with a focus on technology integration and collaborative approaches that have not been explored in depth in previous research. The findings recommend the need for digital literacy training for principals to support technology-based supervision, as well as coaching programs to strengthen collaborative supervision skills. Educational institutions are also advised to adopt policies that support the implementation of these strategies. This research contributes to the development of a more adaptive and effective educational supervision model, as well as being a reference for policy makers and educational practitioners in designing school leadership improvement programs.